(untitled) (Communication & Society, 2015)
This article deals with the representation of reality in documentary and describes a new category of documentary, namely, the objectifying documentary. The objectifying documentary originated in the 2000s, with examples such as Bosnia. Lost Images (2003), and questions a certain type of war propaganda. It pursues two goals: to deconstruct the conventions of the realist style and reveal the artifice behind its supposed immediacy and claim to provide “evidence” of what happened; and to tell a story from a rational, “objectified” point of view. It therefore takes on the appearance of an epistemological tool informed by scientific rationality. In this paper I first describe the characteristics of the realist style in documentary, which was hegemonic until the end of the twentieth century. I then develop the concept of the objectifying documentary and describe its visual and narrative strategies. My methodology is that of aesthetic analysis, as proposed by Corner (2003). I illustrate the concept of the objectifying documentary through the case study of a realist-style news report on the killing of Muhammad Al-Durrah in 2000, which has since been objectified by the documentary Das Kind, der Tod und die Wahrheit (2009). In the last section I analyse one of the most powerful visual strategies for constructing documentary objectivity, namely, the manipulation of temporality. In the conclusions I reflect on the presumed rationality and scientific nature of objectifying documentaries and their epistemic ideology